The study on numerical methods at dynamic modeling of electron bunches in one-dimensional plasma - Sidelnikov, G.L.; Starovoytov, A.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
Several numerical methods used to model the dynamics of electron bunches in one-dimensional plasma are considered. Some a posteriori estimates are studied. A number of conclusions are drawn regarding the applicability of these methods.